PENGARUH METODE CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KEMAMPUAN BERPIKIR INDUKTIF MATERI DAUR AIR PADA SISWA KELAS V SDIT BUNAYYA KABUPATEN TANGERANG - Yeni Nuraeni; Annisa Widya Ayuning Tyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2016)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) method on inductive thinking skills concept of recycling water. The method used is a quasi experimental methods. This study was conducted in SDIT Bunayya Tangerang. The population is 36 students in grade five and the samples consisted of two groups, the experimental group who were 18 students and a control group which also totaled 18 students. The technique of this sample is saturated sample. The experimental group is a group that used the Contextual Teaching and Learning (CTL) method, while the control group is the group that used the conventional method. The instrument used in the form of the test is instrument with the type of the description test. Based on the hypothesis test was using t-test with a confidence level of 95% indicates gained value t_count = 5,769 and t_(table )= 2.042. t_count value is greater than t_(table ) it can be concluded that there is a significant relationship between learning of Contextual Teaching and Learning (CTL) method on student inductive thinking. Keywords :Contextual Teaching and Learning (CTL) method, Inductive Thinking Skills